The Political Economy of Educational Content and Development: Lessons from History - Davide Cantoni; Noam Yuchtman (Center for Economic Studies and ifo Institute (CESifo), 2013)
Beyond years of schooling, educational content can play an important role in the process of economic development. Individuals' choices of educational content are often shaped by the political economy of government policies that determine the incentives to acquire various skills. We first present a model in which differences in human capital investments emerge as an equilibrium outcome of private decisions and government policy choices. We then illustrate these dynamics in two historical circumstances. In medieval Europe, states and the Church found individuals trained in Roman law valuable, and eventually supported productive investments in this new form of human capital. In late 19th-century China, elites were threatened by the introduction of Western science and engineering and continued to select civil servants who enjoyed substantial rents based on their knowledge of the Confucian classics; as a result, investments in productive, modern human capital were not made.
Keywords: N30; I25; O11; O43; 330; educational content; educational institutions; political economy; development